If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10(s + 3) = -46 Reorder the terms: -10(3 + s) = -46 (3 * -10 + s * -10) = -46 (-30 + -10s) = -46 Solving -30 + -10s = -46 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '30' to each side of the equation. -30 + 30 + -10s = -46 + 30 Combine like terms: -30 + 30 = 0 0 + -10s = -46 + 30 -10s = -46 + 30 Combine like terms: -46 + 30 = -16 -10s = -16 Divide each side by '-10'. s = 1.6 Simplifying s = 1.6
| 33+77=x-4 | | -5(3x-25)=2(x-12)-21 | | x+(6x-9)+3=180 | | x^3+4=x^2-1 | | x^2+4x+3y+7=0 | | 7/2x2/3:1/4 | | 0.4793/-2.6217=x | | tan55=x/12 | | 10=-4x(2x+-1) | | -73=4x-13x-9 | | 6+2x=3(-x+2)-20 | | 3/7*3/7 | | 3(2x+15)=12 | | 5x^2-12x-161=0 | | 0.4793/-2.217 | | 0.4793/-2.217=x | | X/8-7/4 | | (3+6I)(5-I)= | | -5/6n= | | 8x-8y=-2 | | 16x^3-33x+2=0 | | 5x^2-12x-227=0 | | -8x-9=-15-7x | | 12x^4y^3/2x^3y^7 | | 100+x+y=144 | | z^2-8z+1=0 | | g(4)=3x^2+5 | | 7n-5n+18=-4 | | 2p+10=20-4p | | 6(3x+7)=35 | | 8x-7y=38 | | 9h=8h-3 |